The end of Education, or what do Trans-humanists dream of - Klichowski, Michał (My University, 2015)
Trans-humanism is a current of thinking that propagates the creation of technologies which serve to overcome human biological limitations. However, trans-humanists want to create not only technologies that make it possible to improve the man, but also to fully liberate their mind from the body. Their desire is to move the human mind to a machine and lead to the creation of super intelligence. What is more, it was revealed in the article that trans-humanists also propagate the elimination of traditional education. They believe that technologies which liberate from the body and increase intelligence are more effective than education.
Keywords: trans-humanism; transhumanism; posthuman; post-human; posthumanism; post-humanism; future of education; technological singularity; nano robots; genetic engineering; man-machine interface; nanorobots